KESIAPSIAGAAN KANTOR KESEHATAN PELABUHAN KELAS II DUMAI DALAM MENGHADAPI RISIKO WABAH PENYAKIT MONKEYPOX (Mpox) BULAN DESEMBER 2023 - Suparno, Suparno; Yunita, Jasrida; Fitri, Yenti (Ensiklopedia of Journal, 2024)
World Health Organization (WHO) once declared Mpox a Public Health Emergency of International Concern (PHEIC). The cumulative number of cases as of September 26th  2023 was 90,618 cases with 157 deaths reported from 115 countries. Until the 51st week, Indonesia reported 71 cases with 56 recovered cases.  Port Health Office (KKP)of Dumai as one of the points of entry at the country's entrance is required to be able to implement disease prevention. The aim of this research is to describe the preparedness of the KKP Dumai in facing the risk of the Mpox disease outbreak entering through the Dumai port. The method in this research is qualitative, with 3 informants, taking informants based on purposive sampling. The research results show that human resources at the KKP  Dumai are sufficient and their competence is also adequate, but there is a need to refresh the Rapid Action Team. In terms of facilities and infrastructure, they are sufficient and in good condition. However, the use of thermal scanners at passenger ports needs to be paid more attention because the results are influenced by environmental temperature, and the KKP Dumai does not yet have an isolation room. In terms of coordination, it needs to be improved again. Existing contingency plan documents need to be simulated and there is no cooperation document between the KKP and RSUD. The conclusion of this research is that Port Health Office i Class II Dumai is not yet optimal in carrying out its preparedness, therefore it is necessary to form a TGC Decree, improve coordination with cross-sectors and cross-programs.Keywords: Preparedness, Coordination, Mpox, facilities & infrastructure, human resources